PERBANDINGAN EFISIENSI BALOK KOLOM BETON DAN KOLOM BAJA DI BANGUNAN MUSEUM MPU PURWA KOTA MALANG - Mesquita, Zerico Corrreia; Wijaya, Handika Setya (eUREKA : Jurnal Penelitian Teknik Sipil dan Teknik Kimia, 2019)
The beam is a wake up space bounded by 6 rectangle, where each side of the rectangle with the appropriate connecting one side of the rectangle, and the rectangle is congruent. Concrete and steel are the two types of material structure commonly used in the construction of a building. Both types of the material sometimes mutually help each other, but can also stand alone on its own, so a lot of structures with similar form and function can be built with concrete or steel. Concrete is a material that was relatively strong against a load of press but weak against load pull. To obtain the relative structure. strong against load-pull, then the added steel reinforcement inside it. A combination of concrete and steel reinforcement is known by the name of concrete. From the results of the calculations and analysis that there is a comparison between the budget cost of the reinforced concrete and steel structures with the difference between the cost of RP 156.261.84. So from a comparison of both the material turns out to be more economical structures reinforced concrete 10%(4).